La Biblioteca Histórica Marqués de Valdecilla de la Universidad Complutense: un centro de apoyo a la investigación y la docencia - Santos Aramburu, Ana (Cuadernos de Historia Moderna, 2006)
The Historical Library “Marqués de Valdecilla” of the Universidad Complutense de Madrid assembles the collections of the educational institutions that have belonged to the University throughout its history. Since its foundation in the late 15th century by Cardinal Cisneros and until the mid-19th century, it opened its doors to numerous prestigious educational institutions and allowed its bookshelves to be shared among their libraries. The Colegio Mayor de San Ildefonso and the Colegios Menores de Alcalá, the Real Colegio de Medicina y Cirugía de San Carlos and the Reales Estudios de San Isidro (formerly, Colegio Imperial de los Jesuitas), together with many other institutions and private libraries, developed a magnificent collection of over 3,000 manuscripts, 728 incunabula and almost 100,000 books dated between the 16th and 19th centuries. The content of this collection bears the hallmark of the evolution of science, thought and education in Spain over the last 500 years. It is no wonder that the Historical Library “Marqués de Valdecilla” has earned a reputation for being a project of the utmost importance, not only because it promotes education and research within the University, but also because it safeguards and disseminates its bibliographic heritage.